Constitutive representation and damage degree index for the layered rock mass excavation response in underground openings. (April 2017) - Xu, Ding-Ping; Feng, Xia-Ting; Chen, Dong-Fang; Zhang, Chuan-Qing; Fan, Qi-Xiang
Highlights: A transversely isotropic elastic–plastic model for layered rock mass was proposed. The failure approach index under transversely isotropic condition was presented. The combined application of the model and the index was provided. Abstract: In this study, a layered rock mass was regarded as a composite material, composed of interlayered intact rocks and bedding planes. Based on this assumption, we developed a transversely isotropic elastic–plastic model to describe the elastic response and post-peak failure behavior based on the Mohr–Coulomb and maximum tensile-stress criteria. Then, we proposed a damage index to estimate the damage degree of layered rock mass during excavation based on the developed model. The numerical simulation of the conventional uniaxial tests indicated that the failure mode and strength predictions of the model were in well agreement with the physical model test results. The index distribution was also shown to be more effective than the plastic zone distribution in identifying layered rock mass failure. The combined application of the mode and the index to assess the stability of the rock mass around the diversion tunnels at the Wudongde hydropower station in China showed that they could accurately estimate the locations and the depth of the potential collapses. Therefore, they are of significant practical value in the stability evaluation of layered rock mass surrounding underground openings.